1993
DOI: 10.1016/0735-1097(93)90827-n
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter investigation of coronary stenting to treat acute or threatened closure after percutaneous transluminal coronary angioplasty: Clinical and angiographic outcomes

Abstract: The early multicenter experience suggests that this stent is a useful adjunct to coronary angioplasty to prevent or minimize complications associated with flow-limiting coronary artery dissections previously correctable only by surgery. Although this study was not randomized, it demonstrated a high technical success rate and encouraging results with respect to the low incidence of emergency coronary artery bypass graft surgery and myocardial infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
108
1
5

Year Published

1996
1996
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 348 publications
(122 citation statements)
references
References 13 publications
8
108
1
5
Order By: Relevance
“…Although the usefulness of emergency stent implantation over that of repeat balloon inflations has never been documented in a randomized trial, multiple observational reports have consistently illustrated the advantages of coronary stents as "bailout" devices (Table 1). [3][4][5][6][7][8][9][10] In the largest case series, George et al 4 reported successful deployment of the Gianturco-Roubin stent in 95.4% of 494 patients with abrupt or threatened abrupt closure during angioplasty. Only 4.3% of patients in this series required emergency bypass surgery, a clear improvement compared with rates typically of Ͼ20% in the prestent era.…”
Section: Coronary Stents Stents As "Bailout" Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the usefulness of emergency stent implantation over that of repeat balloon inflations has never been documented in a randomized trial, multiple observational reports have consistently illustrated the advantages of coronary stents as "bailout" devices (Table 1). [3][4][5][6][7][8][9][10] In the largest case series, George et al 4 reported successful deployment of the Gianturco-Roubin stent in 95.4% of 494 patients with abrupt or threatened abrupt closure during angioplasty. Only 4.3% of patients in this series required emergency bypass surgery, a clear improvement compared with rates typically of Ͼ20% in the prestent era.…”
Section: Coronary Stents Stents As "Bailout" Devicesmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12] Based on these advantages, stent implantation is used in approximately half of all percutaneous interventions in the United States. However, despite their proven benefits, coronary stents continue to be accompanied by several theoretical and practical limitations: they are costly, typically associated with a more marked degree of neointimal formation than balloon angioplasty, and difficult to use with some lesion subsets such as bifurcation stenoses, and they have engendered the new and difficult-to-treat entity of in-stent restenosis.…”
mentioning
confidence: 99%
“…Apesar de que as razões para implante de stents sejam bastante dependentes do médico executando o procedimento, stents são geralmente utilizados em pacientes que, após angioplastia com balão, apresentam lesões residuais que limitam o fluxo sangüíneo ou dissecções complexas [94][95][96][97] . Stents também são utilizados quando um resultado obtido com o balão é inadequado (>30% de estenose residual) 98 e para lesões com morfologia desfavorável, nas quais a angioplastia com o balão torna-se improvável de produzir resultados adequados, como em pontes safenas [99][100][101] ou oclusões crônicas [102][103][104][105] .…”
Section: Abciximab E Stentsunclassified
“…No mesmo ano, Buchwald e col descreveram os resultados iniciais com o stent Wiktor 13 , com um índi-ce de trombose de 17,7%. O registro do stent de GianturcoRoubin teve início em 1988 e os resultados dos primeiros 518 pacientes tratados mostraram uma diminuição expressiva nos índices de infarto agudo do miocárdio (IAM) na fase hospitalar (5,5% x 56%) e de cirurgia de emergência (4,3% x 35%) 14 após oclusão aguda, em comparação com o registro de ATC de 1985de ATC de -1986 do National Heart, Lung and Blood Institute (NHLBI) dos Estados Unidos 15 . Estes dados foram apresentados ao Food and Drug Administration (FDA) em 1992, que aprovou a prótese para tratamento da oclusão coronária aguda pós-ATC.…”
unclassified